Directions for improvement of the system of labor protection management at a pharmaceutical enterprise using digital technologies - Lisna, Anastasia; Kovalenko, Svitlana; Litvinova, Olena (Annals of Mechnikov’s Institute, 2023)
Introduction: The relevance of the research is due to the need to develop and improve the system of labor protection management at pharmaceutical enterprises in the digital economy. Therefore, occupational safety should become a priority for both pharmaceutical managers and employees. After all, today it is more profitable to invest in creating safe working conditions than then carry colossal material costs in the form of fines, assistance to the families of victims, restoration of premises destroyed after accidents, repair of damaged equipment and equipment. That is why the improvement of the system of labor protection management at pharmaceutical enterprises using digital technologies is an important question of the time. Aim. The aim of the study is to consider the prospects and problems of implementing digital technologies in the system of labor protection management, as well as ways to increase the efficiency of using digitalization by specialists in labor protection to improve labor safety indicators at the pharmaceutical enterprise. Materials and methods: To achieve the aim of the study, foreign and domestic scientific literature were analyzed. Informational, retrospective, graphic, statistical, and logical methods were used. Results and discussion. The relevance of the digitalization of the system of labor protection management in the pharmaceutical industry has been substantiated. A review of the directions for the development of digital technologies in the field of labor protection in pharmaceutical enterprises was conducted. The components of the digitalization of the system of labor protection management in pharmaceutical enterprises were systematized. Modern tools for implementing digital technologies to ensure the safety of production processes at pharmaceutical enterprises have been analyzed. The conditions that determine the implementation of digitalization in the system of labor protection management have been identified. Conclusion. It has been proven that the implementation of innovative solutions in the system of labor protection management, simplification of document flow, and digitalization of the main processes in labor safety will prevent industrial injuries, increase labor productivity, and optimize communications among employees of pharmaceutical enterprises. Certainly, the problem raised in this study does not reveal the whole range of issues related to the implementation of scientific and practical approaches to the national pharmacy regarding the impact of digitalization on the system of labor protection management. The complex of issues related to the substantiation of the choice of directions of improvement of the system of labor protection management at pharmaceutical enterprises in the context of the digital economy, etc., remains unresolved, which will determine the prospects for our further research. Keywords: pharmaceutical enterprise, system of labor protection management, digitization, digital technologies.